Selective removal and recovery of gallium and germanium from synthetic zinc refinery residues using biosorption and bioprecipitation - Saikia, Sudeshna; Costa, Rachel B. [UNESP]; Sinharoy, Arindam; Cunha, Mirabelle P.; Zaiat, Marcelo; Lens, Piet N.L. (Elsevier, 2022)
The depletion of primary ores, the environmental concerns related to mining activities, and the need to promote circular economy has drawn attention to the recycling of metallic compounds. Bio-based technologies are suitable for metal recovery, as they operate under mild conditions (ambient temperature and pressure) and are ideal for treating low-concentration waters. This study compared the effectiveness of adsorption and precipitation for the removal and recovery of gallium, germanium and zinc. Adsorption of the metallic ions on elemental forms of sulfur (S0), selenium (Se0) and tellurium (Te0), both of chemical and biological sources, was tested. Biosorption onto elemental forms of S0bio, Se0bio and Te0bio effectively removed Ga and Zn. The highest removal efficiency (ղ) was obtained for Ga onto the adsorbent Te0bio (69 ± 0.4%), with an adsorption capacity (q) of 74 mg Ga (g Te0bio)−1, followed by Zn (ղ = 40 ± 0.7%) with 43 mg Zn (g Te0bio)−1. Precipitation with chemical and biogenic sulfide at different metal to sulfide (Me/S) ratios was also assessed. Biologically produced sulfide was more efficient for Ga and Zn compared to chemical sulfide. Precipitation with biogenic sulfide was efficient for the removal of Ga (ղ = 59.9 ± 2.6%) and Zn (ղ = 44.2 ± 3.0%). The lowest ratio between metal to sulfide (Me/S = 0.2) achieved higher zinc removal efficiencies, whereas gallium removal was more efficient at Me/S = 1.5. None of the tested methods allowed for recovery of Ge. Biosorption and bioprecipitation gave nevertheless high removal and recovery of Ga and Zn.
Keywords: Adsorption; Gallium; Germanium; Precipitation; Tellurium; Zinc